Digenesis: Flipbook-Based Teaching Materials on Civics Education for Grade IV Elementary School - Pramestya, Denty; Witanto, Yuli (Journal for Lesson and Learning Studies, 2024)
The use of teaching materials that are less interactive and do not maximize the use of technology is a problem that can affect student learning outcomes. This study aims to produce digital teaching materials based on flipbook in Civic Education class IV elementary school subjects that are practical, feasible, effective, and can improve student learning outcomes. The implication of this research is that the learning process becomes more creative and innovative because of the digital teaching materials that involve technology in its use. The research method used in this research is the Research & Development (R&D) method which was developed with the ADDIE model. The subjects involved included 1 material expert, 1 media expert, 1 teacher, and 22 fourth grade students. The data collection techniques used are test techniques in the form of pretests and post-tests, and non-test techniques in the form of observation results, teacher interviews, and questionnaires. Meanwhile, the data analysis technique was carried out by practicality test and N-Gain test. The results of the validation of teaching materials by material experts of 90,6% and media experts of 95% show that the teaching materials "DIGINESIA" have met the criteria very feasible to be used as learning support. Based on the results of the pretest and post-test, it is known that the teaching materials “DIGINESIA” are effective for improving student learning outcomes as indicated by the results of an average increase of 45,8 and the N-Gain test results obtained of 0,73 with a high category. The response questionnaires distributed to teachers and students obtained 100% and 97,7% with very positive categories. From these results, it can be concluded that the teaching material “DIGINESIA” is feasible, practical, effective, and can improve the learning outcomes of grade IV students in the Civic Education subject.